Encountering violence: the policing of violent masculinities in Roma settlements in Rome - Solimene, Marco (Gender and violence in Romani and Traveller lives, 2025)
Examining the connection between whiteness, gender, masculinity, politics, and fieldwork, this chapter proposes a reflection on the authorâ€™s positionality as a male, non-Roma ethnographer in contexts characterised by deep and pervasive forms of intersecting violence. The chapter focuses on an event that took place during ethnographic fieldwork 15Â years ago in an informal settlement in Rome, and it outlines how Roma coped with police control and repression. It also describes how the heightened anti-Roma sentiments permeating Italian society at the grassroots and institutional levels affected relations and interactions within the Roma domestic space. Finally, the chapter highlights the dilemmas and pitfalls triggered by the ethnographerâ€™s encounter with violence; it explores the problematic character of defining acts, interactions and events as violent; and it discusses the risk of the ethnographer unwillingly partaking in, contributing to and perpetrating violence.